Frequent GNAQ and GNA14 Mutations in Hepatic Small Vessel Neoplasm. (September 2018) - Joseph, Nancy M.; Brunt, Elizabeth M.; Marginean, Celia; Nalbantoglu, ILKe; Snover, Dale C.; Thung, Swan N.; Yeh, Matthew M.; Umetsu, Sarah E.; Ferrell, Linda D.; Gill, Ryan M.
Abstract : Hepatic small vessel neoplasm (HSVN) is a recently described infiltrative vascular neoplasm of the liver, composed of small vessels. Although the infiltrative nature can mimic angiosarcoma, HSVN are thought to be benign or low-grade neoplasms because they lack cytologic atypia and increased proliferation. To characterize the molecular pathogenesis of HSVN, we performed both targeted panel sequencing and exome sequencing on 18 benign or low-grade vascular neoplasms in the liver including 8 HSVN, 6 classic cavernous hemangioma (CH), and 4 variant lesions (VL) with overlapping features between HSVN and CH. All 18 lesions had simple genomes without copy number alterations. In total, 75% (6/8) of HSVN demonstrated known activating hotspot mutations in GNAQ (2/8, p.Q209H) or GNA14 (4/8, p.Q205L), and the remaining 2 had the same missense mutation in GNAQ, p.G48L, which has not been previously described. 25% (1/4) of VL had a hotspot GNAQ p.Q209H mutation and another VL had a GNAQ p.G48L mutation. Known pathogenic mutations were not identified in any of the 6 CH. These data suggest that HSVN share a similar molecular biology to several other vascular lesions (congenital hemangioma, tufted angioma, anastomosing hemangioma, lobular capillary hemangioma, and kaposiform hemangioendothelioma) recently reported to have GNAQ, GNA11, or GNA14 mutations. Abstract : Supplemental Digital Content is available in the text.